Athlete learning in elite sport. A cultural framework (Routledge, 2019)
Elite athletes lead a particular way of life, which creates significant learning and shapes their selves. This is the first sociological-pedagogical text to conceptualise athlete learning in elite sport and across athletic careers. It outlines theories of learning and argues for a cultural perspective capturing contextual influence, temporal changes, individual dispositions, and subjectivity.